2010
DOI: 10.1183/09031936.00182009
|View full text |Cite
|
Sign up to set email alerts
|

Aclidinium inhibits cholinergic and tobacco smoke-induced MUC5AC in human airways

Abstract: Mucus hypersecretion and mucin MUC5AC overexpression are pathological features of chronic obstructive pulmonary disease (COPD). This study examines the inhibitory effect of aclidinium, a new long-acting muscarinic antagonist, on MUC5AC expression in human airway epithelial cells.MUC5AC mRNA (RT-PCR) and protein expression (ELISA and immunohistochemistry) were studied in human bronchial tissue and differentiated human airway epithelial cells activated with carbachol (100 mM) or cigarette smoke extract in the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 29 publications
2
44
0
1
Order By: Relevance
“…Previous reports have suggested that cigarette smoke may activate a non-neuronal cholinergic system in different cell types, including airways and human lung fibroblasts. For example, we have recently shown that CSE promotes synthesis and release of the mucin MUC5AC in differentiated bronchial epithelial cells by a mechanism mediated by release of acetylcholine, and can be inhibited by aclidinium bromide [8]. Furthermore, human lung fibroblasts from COPD patients have shown an increase of muscarinic receptors, as well as ChAT expression, an effect that was mimicked in healthy lung fibroblasts after CSE exposure [9].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous reports have suggested that cigarette smoke may activate a non-neuronal cholinergic system in different cell types, including airways and human lung fibroblasts. For example, we have recently shown that CSE promotes synthesis and release of the mucin MUC5AC in differentiated bronchial epithelial cells by a mechanism mediated by release of acetylcholine, and can be inhibited by aclidinium bromide [8]. Furthermore, human lung fibroblasts from COPD patients have shown an increase of muscarinic receptors, as well as ChAT expression, an effect that was mimicked in healthy lung fibroblasts after CSE exposure [9].…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, a dysfunction of a non-neuronal cholinergic system may contribute to the pathophysiology of asthma and COPD [7]. It has been shown that anticholinergic treatment inhibits cigarette smokeinduced mucin hypersecretion in human bronchial epithelial cells [8], as well as cigarette smoke-induced lung fibroblast proliferation [9]. Furthermore, choline acetyltransferase (ChAT), the intracellular enzyme responsible for acetylcholine production, is upregulated in both lung fibroblasts from COPD patients and fibroblasts stimulated with cigarette smoke [9].…”
mentioning
confidence: 99%
“…The muscarinic agonist carbachol upregulates MUC5AC expression in these cells by activation of muscarinic receptors and transactivation of epidermal growth factor receptors (EGFR). Aclidinium has been shown to decrease this effect in vitro (67). Treatment with tiotropium has also been demonstrated to improve mucociliary clearance, as reflected by reduced nasal clearance time, in patients with COPD (68).…”
Section: Reduction Of Mucus Hypersecretion and Improvement Of Mucocilmentioning
confidence: 99%
“…MUC5AC is the predominant mucin gene expressed in human airway epithelial cells (66). The muscarinic agonist carbachol upregulates MUC5AC expression in these cells by activation of muscarinic receptors and transactivation of epidermal growth factor receptors (EGFR).…”
Section: Reduction Of Mucus Hypersecretion and Improvement Of Mucocilmentioning
confidence: 99%
“…Furthermore, the expression of the predominate mucin gene in human airways, MUC5AC, is augmented in asthmatics, patients with COPD, and normal smokers [66]. This overexpression can be blocked by aclidinium [67]. Acetylcholine has also been implicated in cell signaling that leads to fibrosis and airway remodeling in smokers [68].…”
Section: And Special Populationsmentioning
confidence: 96%